Hoax : Donald Trump, Fox News, and the dangerous distortion of truth - Stelter, Brian (One Signal Publishers/Atria, 2020)
The CNN correspondent examines Donald Trump's controversial relationship with the Fox News network and discusses the tensions at the network between Trump loyalists and the few remaining journalists.